Marketing Management Development for Training Improvement English Learning “Conversation Club” - Indahwati Indahwati; Ruswiati Suryasaputra; Lusy Tunik Muharlisiani (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of this research is to find out how to manage marketing, increase the quantity of the “Conversation Club” learning training.